2021
DOI: 10.3390/microorganisms9081735
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and Metabolites of Endoparasitic Nematophagous Fungus Drechmeria coniospora YMF1.01759 against Nematodes

Abstract: Plant parasitic nematodes cause severe damage to crops. Endoparasitic nematophagous fungi (ENF) are a type of important biocontrol fungi, which can cause disease or kill nematodes by producing various spores. As a major ENF, Drechmeria coniospora displays certain potential for controlling plant-parasitic nematodes. In this study, the pathogenicity and secondary metabolites of the endoparasitic fungus D. coniospora YMF1.01759 were investigated. The strain D. coniospora YMF1.01759 had high infection efficiency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
8
0
2
Order By: Relevance
“…Other strategies contribute to the process of attraction, adhesion and cuticular degradation, penetration, and the invasion of nematode bodies, as well as eventually the fungal nutrition from the nematode internal tissues [ 46 ]. These mechanisms are developed in a sequence of biological, physiological and biochemical steps as follows: (a) production of attractants molecules that mimic sexual and food olfactory clues to lure nematodes [ 47 ]; (b) production of adhesive extracellular polymers that attach to the nematode cuticular surface contributing to the trapping process [ 48 ]; (c) nematode paralysing substances or nematotoxins [ 49 ]; (d) an enzymic system specially directed to degrade the nematode cuticle components to traverse and penetrate the cuticular wall [ 50 , 51 ]; and (e) production of nematocidal metabolites [ 16 , 52 , 53 ]. The results obtained in the present study showed differences in the nematocidal activity of FCF of A. musiformis growing in different media.…”
Section: Discussionmentioning
confidence: 99%
“…Other strategies contribute to the process of attraction, adhesion and cuticular degradation, penetration, and the invasion of nematode bodies, as well as eventually the fungal nutrition from the nematode internal tissues [ 46 ]. These mechanisms are developed in a sequence of biological, physiological and biochemical steps as follows: (a) production of attractants molecules that mimic sexual and food olfactory clues to lure nematodes [ 47 ]; (b) production of adhesive extracellular polymers that attach to the nematode cuticular surface contributing to the trapping process [ 48 ]; (c) nematode paralysing substances or nematotoxins [ 49 ]; (d) an enzymic system specially directed to degrade the nematode cuticle components to traverse and penetrate the cuticular wall [ 50 , 51 ]; and (e) production of nematocidal metabolites [ 16 , 52 , 53 ]. The results obtained in the present study showed differences in the nematocidal activity of FCF of A. musiformis growing in different media.…”
Section: Discussionmentioning
confidence: 99%
“…1 H-NMR (CDCl 3 , 600 MHz) δ: 4.06 (2H, m, H-3), 5.67 (1H, s, H-7), 1.03 (3H, s, H-18), 0.62 (3H, s, H-19), 1.02 (3H, d, J = 6.9 Hz, H-21), 5.25 (2H, m, H-23/H-24), 0.83 (3H, d, J = 6.9 Hz, H-26), 0.84 (3H, d, J = 6.9 Hz, H-27), 0.92 (3H, d, J = 6.9 Hz, H-28); 13 Assays were performed in 24-well cell culture plates. M. incognita egg acquisition [10]: oocysts were picked from the root knots of susceptible tomato and washed of impurities with ddH 2 O, shaken with 0.5% NaClO for 3 min, and then filtered with a 500-mesh sieve to remove NaClO, rinsed with sterile water 3 times, shaken with 2% NaClO solution for 3 min to obtain eggs, and subjected to 10 µL microscopic examinations after completion to prevent excessive cracking. For the second stage juveniles of M. incognita (J2), the obtained eggs were hatched in a 25 • C incubator, and M. incognita (J2) were collected for later use.…”
Section: Extraction and Separation Of Metabolitesmentioning
confidence: 99%
“…In general, the metabolites of microorganisms often play an important role in biological control of nematode. For example, 5-hydroxymethylfuran-2-carboxylic acid was isolated from Drechmeria coniospora and possessed nematocidal activity against M. incognita [ 10 ], and leucinostatins obtained from Paecilomyces lilacinus showed nematocidal activity [ 11 ], while other compounds such as phenolic acids and sesquiterpenoids were obtained from Paecilomyces lilacinus and exhibited nematocidal activity [ 11 , 12 ]. Therefore, it is necessary to carry out research on active metabolites from biocontrol potential fungus P. lavendulum YMF1.00683.…”
Section: Introductionmentioning
confidence: 99%
“…Jansson, 1985is an endoparasitic nematophagous fungus used as a bioagent against nematodes. An extract from SDAY (10.0 g bacterial peptone, 10.0 g yeast extract, 40.0 g glucose, 18.0 g agar, 1 L water) medium offungal isolate of D. coniospora YMF1.01759 showed nematicidal activity against M. incognita , resulting in 99.1% mortality at 5 mg m/L at 72 h. EtOAc extract obtained from crude extract of SDAY attained 98.0% mortality of juveniles at 1 mg mL −1 at 72 h. From EtOAc extract, 13 metabolites were isolated and identified, and among them, 5-hydroxymethylfuran-2-carboxylic acid (1) at a concentration of 400 µg mL −1 exhibiteda toxic effect on M. incognita , resulting in 100% mortality of J2s after 72 h. The compound also inhibited egg hatching, as the number of hatched J2s from one egg mass was 11.17 at 200 µg mL −1 after 3 days [ 98 ].…”
Section: Biocontrol Agents Against Root-knot Nematodesmentioning
confidence: 99%